TMIC-28. GLIOBLASTOMA EXPLOITS CELL SURFACE GLYCOSYLATION-MEDIATED IMMUNE REGULATORY CIRCUITS FOR IMMUNE ESCAPE. (5th November 2018) - Dusoswa, Sophie; Verhoeff, Jan; Abels, Erik; Breakefield, Xandra; Noske, David; Würdinger, Tom; Broekman, Marike; Van Kooyk, Yvette; Garcia-Vallejo, Juan
Abstract: Glioblastoma is the most aggressive brain malignancy, for which conventional therapy has failed to achieve major improvements in survival since 2005. Glioblastoma-associated immune infiltrates are dominated by tumour-associated macrophages (TAM), which could be the key mediators of immune suppression. Recently we proposed the tumour "glyco-code" as a novel target for immunotherapy, and source for biomarkers. Malignant transformation is associated with aberrant expression of cell surface glycans, which play crucial roles in processes such as migration, angiogenesis and immune modulation. Here we investigated the glioblastoma glycocalyx as a tumour-intrinsic immune suppressive mechanism via tumour infiltrating macrophages. We detected increased expression of tumour-associated truncated O-linked glycans in patient-derived glioblastoma- versus control tissues by immunofluorescence and ELISA based assays. In concert, the macrophage galactose lectin (MGL) receptor, which interacts with truncated O-linked glycans, was overexpressed on glioblastoma infiltrating TAM, also detected by immunofluorescence, and confirmed on RNA level in TCGA data. Unsupervised, high-dimensional mass cytometry (CyTOF) analysis of a murine immunocompetent orthotopic glioblastoma model overexpressing truncated O-linked glycans revealed increased tumor infiltration by CCR2+, PD-L1+ macrophages. At a systemic level, we discovered increased frequencies of CCR2+ peripheral dendritic cells (pDC), and a decrease in CCR2+ monocyte frequencies in the bone marrow of these mice. Moreover, we observed a drastic increase in correlations between glioblastoma infiltrating CCR2+ macrophages and several myeloid cell subsets in the bone marrow using network analysis of frequency correlation statistics. Our results suggest that glioblastomas overexpress truncated O-linked glycans and exploit cell surface glycosylation- mediated immune regulatory circuits for systemic immune modulation and recruitment of suppressive TAM.